1991
DOI: 10.1098/rspb.1991.0056
|View full text |Cite
|
Sign up to set email alerts
|

The incidences and evolution of cytoplasmic male killers

Abstract: Two types of male-killing cytoplasmic gene are distinguished by their time of action. Early male killers strike embryos, whereas late killers, so far only observed in mosquitoes, kill fourth instar larvae. Maternal inheritance of cytoplasmic factors underlies the sex bias in mortality in both instances. However, the evolutionary logic of early and late killing is, it is argued, otherwise different. Early male killing is interpreted in terms of kin selection. The death of male embryos early on allows resources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(101 citation statements)
references
References 62 publications
3
95
0
3
Order By: Relevance
“…R. Soc. B 282: 20152068 efficacy and a benefit provided to the surviving host offspring by killing the infected male embryos [10], and may also depend on their spatial distribution [11]. We showed that a purely vertically transmitted non-MK bacterium, otherwise able to invade the host as a highly efficient male-killer (electronic supplementary material, appendix S3), cannot persist and evolve MK gradually unless at least a bit of HT is present.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…R. Soc. B 282: 20152068 efficacy and a benefit provided to the surviving host offspring by killing the infected male embryos [10], and may also depend on their spatial distribution [11]. We showed that a purely vertically transmitted non-MK bacterium, otherwise able to invade the host as a highly efficient male-killer (electronic supplementary material, appendix S3), cannot persist and evolve MK gradually unless at least a bit of HT is present.…”
Section: Discussionmentioning
confidence: 84%
“…Purely vertically transmitted bacteria (strains with l ¼ 0) which kill infected male offspring with 100% efficacy can successfully establish in the host population if the VT efficacy j and fitness compensation parameter g (equation (2.2)) are high enough [10]. However, highly efficient male-killers might have evolved gradually from less-efficient male-killers, and from bacteria that did not possess any MK ability [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When I ¼ 0, there is no Spiroplasma infection in the host population. Hurst (1991) modeled the invasion of a male killer under the resource release hypothesis; thus, this equilibrium will not be discussed further here. The other equilibrium is reached when I ¼ I 0 ,…”
Section: Wasp Growth Ratementioning
confidence: 99%
“…The latter occurs only when male death allows the symbiont to be transmitted horizontally (e.g., via consumption of the lethargic male). Thus, virulence is sex specific: symbiont-induced mortality is much higher in the horizontally transmitting sex than in the vertically transmitting sex (Hurst 1991;Ebert and Herre 1996).…”
Section: Vertical Transmission Lowers Virulencementioning
confidence: 99%